2005
DOI: 10.1159/000087437
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Mechanism of Saikosaponin-d in Anti-Thy1 mAb 1-22-3-Induced Rat Model of Glomerulonephritis

Abstract: Aims: Mesangioproliferative glomerulonephritis is a common kidney disease and at present, there is no effective treatment. Our previous studies have demonstrated that Sairei-to can significantly prevent progression of experimental glomerulonephritis in rats. Although we have reported that the active component of Sairei-to in treatment of glomerulonephritis was Saikosaponin-d (Ssd), mechanism of Ssd in prevention of mesangioproliferative glomerulonephritis progression is still unknown. Therefore, current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…HK-2 cells were treated with SSD (0,20,40,60,80,100 or 150 μM) for 24 h (A) and were then uniformly treated with the maximum dose of SSD (100 μM) for different periods (0, 6, 12, 24 or 48 h; B). The cells were treated with DDP (0, 2.5, 5, 10, 20 or 30 μM) for 24 h (C) and were pretreated with SSD (100 μM) for different periods (0, 15 min, 30 min, 1 h, 2 h, 4 h, 8 h, 16 h or 32 h) and were pretreated with SSD (20,40,60,80,100 or 150 μM) for 2 h and then were treated with 10 μM DDP (E) for 24 h. Cell viability was determined using the CCK-8 assay according to the absorbance value (A). The data are presented as the mean values ± SD from five independent experiments.…”
mentioning
confidence: 99%
“…HK-2 cells were treated with SSD (0,20,40,60,80,100 or 150 μM) for 24 h (A) and were then uniformly treated with the maximum dose of SSD (100 μM) for different periods (0, 6, 12, 24 or 48 h; B). The cells were treated with DDP (0, 2.5, 5, 10, 20 or 30 μM) for 24 h (C) and were pretreated with SSD (100 μM) for different periods (0, 15 min, 30 min, 1 h, 2 h, 4 h, 8 h, 16 h or 32 h) and were pretreated with SSD (20,40,60,80,100 or 150 μM) for 2 h and then were treated with 10 μM DDP (E) for 24 h. Cell viability was determined using the CCK-8 assay according to the absorbance value (A). The data are presented as the mean values ± SD from five independent experiments.…”
mentioning
confidence: 99%
“…Previous reports have demonstrated that saikosaponin D was effective in anti-Thy1 mAb-induced nephritis [26] and anti-GBM nephritis [27] in rats. Anti-GBM nephritis during the heterologous phase and anti-Thy1 nephritis were mainly developed by binding of heterogeneous antibodies to the GBM or mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This may herald a novel approach for further studies of Ssd as a candidate for use in the treatment of inflammatory and autoimmune diseases. Li et al [20] reported that Ssd can inhibits the progression of mesangioproliferative glomerulonephritis through reduction of the expression of Transforming growth factor beta 1 (TGF-b1) and the infiltration of macrophages and CD8? T lymphocytes.…”
Section: Therapeutical Potential Of Saikosaponins In Autoimmune Diseamentioning
confidence: 99%